2017
DOI: 10.2196/medinform.6512
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Electronic Medical Record Implementation in Mental Health Care: A Case Study

Abstract: BackgroundElectronic medical records (EMR) have been implemented in many organizations to improve the quality of care. Evidence supporting the value added to a recovery-oriented mental health facility is lacking.ObjectiveThe goal of this project was to implement and customize a fully integrated EMR system in a specialized, recovery-oriented mental health care facility. This evaluation examined the outcomes of quality improvement initiatives driven by the EMR to determine the value that the EMR brought to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 21 publications
(43 reference statements)
0
48
0
Order By: Relevance
“…In another, overall productivity increased by around 5% per year post-full EPR implementation98; whilst productivity may initially fall, billing income may increase due to improved coding 99. Furthermore, cost-savings include reduced medication errors, improved implementation of clinical practice guidelines, enhanced infection prevention and cost-effective diagnostic testing100; order-set creation and care pathway redesign have significant benefits 101. Such guideline integration may require calculated and complex variables, hence workflows may require modification to collect such data 102.…”
Section: Resultsmentioning
confidence: 99%
“…In another, overall productivity increased by around 5% per year post-full EPR implementation98; whilst productivity may initially fall, billing income may increase due to improved coding 99. Furthermore, cost-savings include reduced medication errors, improved implementation of clinical practice guidelines, enhanced infection prevention and cost-effective diagnostic testing100; order-set creation and care pathway redesign have significant benefits 101. Such guideline integration may require calculated and complex variables, hence workflows may require modification to collect such data 102.…”
Section: Resultsmentioning
confidence: 99%
“…In some countries with common claims datasets or electronic medical records, mental health care measures have been variably adopted 66,67 . For example, the UK National Health Service has a long tradition of using electronic medical records in primary care for routine quality measurement, most notably through the Quality Outcomes Framework, the largest payment-by-results program in the world.…”
Section: Unique Challenges To Mental Health Care Quality Measurementmentioning
confidence: 99%
“…One of these areas is the abovementioned IAPT initiative, which embedded routine outcome measurementusing validated tools such as the PHQ-9 and the Clinical Outcomes in Routine Evaluation (CORE) -and could demonstrate good outcomes that have led to further funding into the initiative 71 . In Canada, there has been the adoption of mental health care quality measures in electronic medical records 67 . Still, due to long-standing stigmatization and functional challenges, consumers of mental health services may feel burdened by the data gathering.…”
Section: Unique Challenges To Mental Health Care Quality Measurementmentioning
confidence: 99%
“…Examples of major change involving adoption of technology are already underway within the UK National Health Service (NHS), including an organization‐wide change from paper to electronic patient records by 2020 (National Information Board, ), in line with evidence linking electronic notes with improved clinical outcomes in both general hospitals (Amarasingham, Plantinga, Diener‐West, Gaskin, & Powe, ) and mental health services (Riahi, Fischler, Stuckey, Klassen, & Chen, ). In addition, the Nursing Technology Fund, launched in 2013, has provided financial support to enable nurses to incorporate innovative technology in their daily practice, in order to improve efficiency and patient care (NHS England, ).…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing abstracts and confirming by reading full papers, six papers were initially identified as meeting the criteria, with three related to aspects of the same intervention (see Table ). Two further papers (Ben‐Zeev et al, ; Riahi et al, ) were identified through checking citations and references and subsequent citations of the initial list of six (see Table ).…”
Section: Introductionmentioning
confidence: 99%